Development of Clinical Training Models for Comprehensive Emergency Obstetrics and Neonatal Care (Ceonc/Ponek) and Facilitative Supervision for Improving Hospital Performance - Hadijono, Soerjo; Samsudi, Samsudi; Florentinus, Totok Sumaryanto; Noorpramono, Noorpramono (The Journal of Educational Development, 2019)
Training investments and provision of facilities can only mobilize a part of healthcare production machines, and will be successfully drive it if they are fully supported by the local institutions / government and clinical training quality assurance system. In medical education and clinical training, the behaviours and attitudes modeled by professional practitioners are a special mechanisms in which participants will implicitly "learn" various aspects of their professional positions in the future. This study aim is to assess the educational management of a competency-based clinic training of Comprehensive Emergency Obstetric and Neonatal Care (CEONC/PONEK) followed by model simulation and the influence of facilitative supervision as an effort to improve hospital performance. Improving the quality of health services are expected to have significant leverage to reduce morbidity and mortality rates of mothers and neonates in Indonesia. The research was conducted in Dr Kariadi Central Hospital Semarang and Umbu Rara Meha Waingapu General Hospital at East Sumba Regency (East Nusa Tenggara Province) from 2012 to 2016. The research and evaluation conducted only in the process of educational management, so change towards a better state are expected after the intervention. The research was conducted through observational single cohort of pre-posttest design using performance assessment appraisal forms, direct and retrospective assessment which have been prepared for this research, and using primary data taken from the Hospital Management and Information System (SIMRS) database. CEONC skills training with simulation followed by facilitative supervision significantly improves the input and process in both maternal and neonatal hospital service (p < 0.05). Training also has a significant impact on improved team performance (p < 0.05), as well as compliance of health personnel to maternal care standards, although it has not had a significant impact on neonatal health services in both hospitals.